2012
DOI: 10.1089/end.2012.0039
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Reconstruction for Obstructive Megaureter: Single Institution Experience with Short- and Intermediate-Term Outcomes

Abstract: Laparoscopic reconstruction of obstructive MGU offers satisfactory immediate- and intermediate-term outcome without undue prolonged morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Joseph and Gundeti [5] have suggested anterior wall detrusorotomy to achieve straight direction of implanted ureter to prevent ureteral angulation. In the laparoscopic or robotic approach, some authors use intracorporeal excisional tailoring and reimplantation of the ureter in according to the classical Lich-Gregoire technique [5][6][7]. Lopez et al [9] have used Hendren extracorporeal technique for tapering of megaureters in 7 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Joseph and Gundeti [5] have suggested anterior wall detrusorotomy to achieve straight direction of implanted ureter to prevent ureteral angulation. In the laparoscopic or robotic approach, some authors use intracorporeal excisional tailoring and reimplantation of the ureter in according to the classical Lich-Gregoire technique [5][6][7]. Lopez et al [9] have used Hendren extracorporeal technique for tapering of megaureters in 7 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients over 1 year, indications for surgery in 10 cases of POM included progress of hydroureteronephrosis, with deteriorating on MAG3 and breakthrough UTI in spite of continues antibiotic prophylaxis during of 16.1 ± 5.2 months of conservative management. Others 36 patients were operated due to refluxing megaureter (18), megaureter of duplex kidney (8), 6 after failed open reimplantation and 3 after ureterocutaneostomy. Of patients with VUR, seven had a combination of a diverticulum and six had a combination VUR and vesico-ureteral (25) junction obstruction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, open ureteral reparation and reimplantation is the gold standard therapy for primary symptomatic obstructive megaureter. Within the past decade, however, laparoscopic surgery has become popular in urology and has resulted in improved outcomes compared with open surgery, even in reconstruction procedures [2]. Today, the Da Vinci robot-assisted laparoscopic surgery platform (Intuitive Surgical, Sunnyvale, CA), which is characterized by stereoscopic vision and a flexible operating arm, provides us with the distinct advantages of minimally invasive reconstruction of the urinary tract, particularly in intracorporeal reparation and suturing.…”
Section: Introductionmentioning
confidence: 99%
“…Short distal ureteric defects can be managed by laparoscopic ureteroneocystostomy [4,7]. Recently, surgeons have proposed several modifications for laparoscopic ureteroneocystostomy so as to shorten the operation time and reduce the complexity of this operation [9,10,11,12,13]. Nevertheless, Austenfeld and Snow [14] and Mor et al [15] found that women who underwent ureteral reimplantation as children were at higher risk of ureteral obstruction and renal failure during pregnancy.…”
Section: Introductionmentioning
confidence: 99%